Malignant meningioma with intra- and extra-cranial extension: A case report - P, Hazif Backer; Shukla, Anil Kumar; R, Nagesh; V V, Seetha Pramila; G U, Pravin (Indian Journal of Case Reports, 2018)
Meningioma is the most common intracranial benign neoplasm. The malignant transformation of this neoplasm is less frequent. Here, we report the case of a 77-year-old male patient who came to our department with a visible mass in the scalp for 1½ years. The mass was gradually increasing in size, soft in nature, not painful, and associated with the left-sided weakness. His multidetector computed tomography showed lesion which is having an intracranial component with the destruction of a vault with extracranial extension. This imaging modality gives a clear-cut picture of the extent of the lesion, nearby structures, and vascularity to give the surgeon proper guidance in two, three, and four dimensions.